PEMBERDAYAAN BIROKRASI DAN KOMUNITAS - Suradi Suradi (Politeknik Kesejahteraan Sosial, 2003)
Revitalisasi Fungsi dan Tugas Birokrasi Pemerintah bagi Pembanguna.(Bureaucracy and Community Empowerment: Revitalization of Function and Task of Bureaucrat for Community Development.Developing a program and its implementation in social welfare sector is influenced by the policy and strategy chosen by the bureaucracy. Srategy chosen for economic growth or GNP causes less priority in social welfare sector because economical doesn't give any direct benefit. These unreflected thoughts will lead bureucracy to difficulties related to the national, regional and international community development. Community development currently demands some conditions as a consequency of the membership of a state in a regional organization or an international organization as well as of international monetary institutions and other donor states. Regarding to this frame, the bureaucracy revitalization in all level becomes a rational demand and a strategic choice in the efforts to build social welfare for all people.